KESELAMATAN: BERADA DALAM ALLAH BAPA DAN TUHAN YESUS KRISTUS - John Gratias Pakulayuk (Jurnal Euntes, 2022)
What and how is salvation? The Apostle Paul's First Letter to the Thessalonians gives an explanation of salvation. This paper wants to explain Paul’s explanation of salvation argumentatively. For Paul, salvation is manifesting life in God the Father and the Lord Jesus Christ. It is a gift through the events of the death and resurrection of Jesus. Besides that, Paul linked salvation with waiting for the coming of the Lord. He uses the term parousia, which means presence. The salvation that Paul proclaimed through experiencing God’s presence in life now leads to its fulfillment at the end of time.